APPLICATION OF SAGO (METROXYLON SAGU) STARCH IN THE DIET OF NILE TILAPIA, OREOCHROMIS NILOTICUS (LINNAEUS, 1758) JUVENILES ON NUTRIENT DIGESTIBILITY AND DIGESTIVE ENZYMES - Benny Lawrence, Senawi; Mohammad Bodrul, Munir; Roslianah, Asdari (Penerbit UMT, 2021)
Omnivorous fish utilize dietary carbohydrates better due to the efficiency of nutrient digestibility and enzymes in the digestive tracts. However, the effectiveness of nutrient digestibility and digestive enzymes can be affected by different levels of dietary carbohydrates in the diet. Very limited information is known about the effect on nutrient digestibility and digestive enzymes by different levels of sago starch utilization. A 12 - week feeding trial was conducted to identify the effects of sago (Metroxylon sagu) starch in the diet of Nile tilapia, Oreochromis niloticus juveniles on nutrient digestibility and digestive enzyme activities. Six isoenergetic (20.25±1.35 kJ/g) semi-purified experimental diets were formulated which consisted of dietary protein levels (P22%; P26%; P30%) incorporated with C38% and C44% of sago starch as the carbohydrates source. All the diets were designated as D1 (P:22%, C:38%); D2 (P:26%, C:38%); D3 (P:30%, C:38%); D4 (P:22%, C:44%); D5 (P:26%, C:44%) and D6 (P:30%, C:44%), respectively. A control diet used was formulated from corn starch and labelled as D0 (P30%: C40%). The result showed fish fed on treatment D3 (80.12%) had higher nutrients digestibility followed by D2 (77.54%), D1 (74.72%), D0 (69.83%), D6 (65.67%), D5 (57.40%) and D4 (50.29%). Digestive enzymes (amylase, lipase and protease) activities were significantly affected among all diets. Fish fed on diet, D3 showed high amylase (6.54 Umg-1 ), lipase (5.68 Umg-1 ) and protease (0.77 Umg-1 ) activities compared to fish from other diet treatments. Two-way ANOVA result confirmed that the incorporation of different levels of protein and carbohydrate had significantly influenced nutrient digestibility and digestive enzyme activities of O. niloticus juveniles. Overall, fish fed on C38% sago starchbased diets showed positive result and performed better than those fed with C44% diets. The study revealed the ability of O. niloticus juveniles to spare protein with sago starch was at optimum level of C38% combined with P26% and P30% protein level.